The Impactful Academic: Relational Management Education as an Intervention for Impact. (January 2017) - Anderson, Lisa; Ellwood, Paul; Coleman, Charlotte
Abstract : We widen the scope of the impact debate by extending Boyer's theorization of scholarship through Denyer, Tranfield and van Aken's CIMO framework to propose relational management education as an intervention that creates the generative mechanism of co‐production and subsequent impact. In so doing, we propose a new conceptualization of academic impact that occurs through teaching and is situated within a community of inquirers. We offer a critique of current thinking, dominated by the idea that the research paper is the most appropriate unit of analysis by which to measure the excellence and impact of research. We examine the notion of the gap between academics and practitioners and argue that the impact agenda should be widened to include a consideration of how management academics can become impactful through their teaching of practitioners, broadly defined to include the whole range of learners associated with business schools. We propose that for management research to have the potential to change these practitioners, an engagement with knowledge is needed, and that this involves more than translation but the creation of new ideas. Such impact can be brought about by a disruption of, and challenge to, thinking engendered by an approach to management education that we term relational.